Social Media Literacy of Indonesian Female Digital Immigrants in Identifying Hoax News - Yusuf Kurniawan; Diah Kristina; Fitria Akhmerti Primasita; Karunia Purna Kusciati; Mariska Wida Azhari (International Journal of Science and Applied Science: Conference Series, 2022)
This study arose from a premise that female digital immigrants are assumed to be more vulnerable to hoax news on social media and tend to disseminate them due to their “natural” tendency, whereas they have important roles as role models and educators for their children. The research investigates how Indonesian female digital immigrants identify hoax news and how they avoid hoax news on social media. Fifteen women aged between thirty and forty years old with various backgrounds of education and having been using social media were selected as the informants. The data were collected using in-depth interviews and focus group discussions. By employing Critical Discourse Analysis the study reveals that in majority the informants indicate that they are quite careful in responding the news or information found on social media. Accordingly, not all female digital immigrants cannot be considered susceptible to hoax news and hoax news disseminator on social media.